Quantification of borax in sago - Salazar, Christian John Calamucha (2002)
BSTRACT The study established the presence of borax in sago samples from 3 commercial sources. The dehydrated sago samples were boiled twice to typify the commercial practice of preparing sago. The turmeric paper method was first used to screen borax contamination of the sago samples. A semi-quantitative method for borax analysis was developed by combining the steps in the turmeric paper method based on color reactions minus the paper matrix, and the visual spectroscopy using 550 nm wavelength. Results of turmeric paper screening indicated the presence of borax in the dehydrated sago and the boiled samples. Borax levels in the dehydrated sago ranged from 7 g borax/kg sago to 9 g borax/kg sago. The final level of borax in twice boiled sago samples ranged from 1 g borax/kg sago to 4 g borax/kg sago. The total loss for the sago was greater than or equal to 52%. The study recommended the use of sodium tripolyphosphate as replacement for borax. The BFAD should constantly monitor the industry for the prohibitive use of borax and quantify the levels of borax in the sago samples. Proper washing and boiling of sago are recommended to be practiced by the consumers.